Secondary Metabolites from the Stem Bark of Geronggang (Cratoxylum arborescens (Vahl) Bl.)and Ketemau (Cratoxylum glaucum K.) and Their Biological Activities - Sim, Wei Chung (2010)
Phytochemical and biological studies were carried out on two species from the Guttiferae family, Cratoxylum arborescens and Cratoxylum glaucum. The chemical investigation discovered triterpenoids, quinones and xanthones. These compounds were isolated using common chromatographic techniques and were identified using modern spectroscopic techniques such as 1D and 2D NMR, MS, IR and UV. Cratoxylum arborescens (stem bark) afforded friedelin, stigmasterol, fuscaxanthone C and two anthraquinone, vismiaquinone and 3-geranyloxy-6-methyl- ,8-dihydroxyanthraquinone. Meanwhile, studies on Cratoxylum glaucum (stem bark)revealed the presence of three xanthones, α-mangostin, β-mangostin and fuscaxanthone C, along with an anthraquinone, 1,8-dihydroxy-3-methoxy- 6-methylanthraquinone, friedelin, β-sitosterol and betulinic acid. This is the first report of α-mangostin, β-mangostin and betulinic acid from Cratoxylum glaucum. The acetylation of fuscaxanthone C has successfully yielded dimethylmangostin acetate. Antioxidant properties of the crude extracts of these two species were tested using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method and compared to a well known antioxidant, ascorbic acid. The crude methanol extracts of both Cratoxylum arborescens and C. glaucum showed high antioxidant activities with low EC50 values of 10.40 and 7.48 ppm, respectively, and are comparable to that of ascorbic acid, 5.17 ppm. The crude chloroform extract of C. arborescens also gave good activity, with an EC50 value of 31.04 ppm. The total phenolic content of the methanol extracts of both species were measured using Folin-Ciocalteu method. The hexane and ethyl acetate extracts of Cratoxylum glaucum and the hexane and chloroform extracts of Cratoxylum arborescens demonstrated low IC50 values against the MCF7 cancer cell line. Meanwhile, the ethyl acetate and methanol extracts of Cratoxylum glaucum and all the extracts of Cratoxylum arborescens were active against HL-60 cancer cell line. The antibacterial activity test was also carried out using eight bacteria, namely,Bacillus cereus, Micrococcus luteus, Methicillin-Sensitive Staphylococcus Aureus (MSSA), Methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli,Klebsiella pneumonia, Pseudomonas aeruginosa and Enterobacter aerogenes.However, all the crude extracts gave only weak or no inhibition to these bacteria. The larvicidal tests were performed against the larvae of Aedes aegypti using the WHO (1981) standard procedures with slight modifications. All the extracts of Cratoxylum arborescens and C. glaucum were found to be inactive against the larvae of Aedes aegypti.